Intellectual property in education sector : analysis of copyright security issues and challenges - 226369 Dzulnizar Abdul Jabar (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Sains Komputer - Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2007